SUN-598 Phenotypic Study of Meso-Somatous (Roch-Leri) Lipomatosis - Lemaitre, Madleen (J Endocr Soc, 2020)
Background: Lipomatosis is a condition in which multiple lipomas are present on the body. Different entities which are accompanied by multiple lipomas include Proteus syndrome, Cowden syndrome and related disorders due to PTEN gene mutations, MEN1, benign symmetric lipomatosis (Madelung or Launois-Bensaude disease), Dercum’s Disease, familial lipodystrophy, hibernomas, epidural lipomatosis, familial angiolipomatosis, and meso-somatous lipomatosis (LMS) still called Roch-Leri lipomatosis. LMS is characterized by the presence of many discrete, encapsulated lipomas of 2 to 5 cm, painless, at the level of the trunk and forearms. The aim of the present study was to determine the clinico-biological phenotype of LMS, as compared to controls. Patients and methods: In this single-center study (NCT01784289), 18 healthy controls (C) and 11 LMS were included after examining the cohort of 76 patients referred for suspected lipodystrophic syndrome between 2009 and 2019 in the Endocrinology Department of a University Hospital. Clinical (sex, age, weight, BMI, blood pressure (BP), alcohol consumption), metabolic (fasting blood glucose (FBG) and insulin levels, lipid balance, ASAT, ALAT, GammaGT, leptin), immuno-inflammatory (CBC, lymphocyte immunophenotyping), and anthropometric (% of body fat in DEXA, steatosis and intra-abdominal / total abdominal fat ratio (IAF / TAF) in MRI) were evaluated. Results: The following parameters, expressed as % or median, differed significantly between LMS vs. C groups, respectively: weight 100 vs. 69kg (p<0.01), BMI 30.8 vs. 22.7 (p<0.01), systolic BP 140 vs. 115 (p<0.01) and diastolic BP 80 vs. 70 mmHg (p<0.05), gammaGT 74 vs. 18 IU / L (p<0.01), fasting insulin levels 7.3 vs. 4.7 microIU / mL (p<0.05), leptin 28 vs. 5 ng / mL (p<0.01), CD3 (867 vs. 1444 / mm3 (p<0.01), CD4 499 vs 866 / mm3 (p<0.05), CD8 227 vs. 546 (p<0.05), fat mass 41 vs. 22 (p<0.05). Three LMS patients had hepatic steatosis and 3 a first-degree family member with LMS. Percentage of men (63% vs. 52%, FBG, lipid levels, ASAT, ALT, CBC, IAF / TAF (0.25 vs 0.19) did not differ significantly. The number of lipomas was > 5 in 82% of LMS patients and lipomas were localized first to the forearms (82%), then the thighs (73%) and the abdomen (55%). At diagnosis, the age of LMS patients was 20 years old; 55% of the LMS patients had a BMI above 30 and 45% above 25. No patient had excessive alcohol consumption. Five had a history of auto-immuneor inflammatory disease: 1 hyperthyroidism, 1 hypothyroidism, 1 multiple sclerosis, 1 vitiligo, 1 Raynaud syndrome. Conclusion: LMS mainly affects overweight men and is associated with hypertension, hyperinsulinism, increased gammaGT and a decrease in CD3, CD4 and CD8 lymphocytes, suggesting an immune dysregulation, all the more so that 45% had an associated auto-immune/inflammatory disease.